Efforts of Islamic Education Teachers Through the Card Sort Method in Improving Learning Outcomes of Islamic Education in Junior High School - Septianah, Mita; Priansyah, Deni (Edumaspul: Jurnal Pendidikan, 2024)
This research investigates the effectiveness of using the card sort method in improving students' learning achievement in Islamic education. Teachers employ this method as a learning strategy to facilitate understanding of complex concepts in Islamic religion. The research approach is qualitative, with a field study design conducted at the research site with the goal of description. Data collection techniques include interviews, observations, and documentation. After conducting observations and research in the field, the results indicate that using the card sort method significantly enhances students' understanding of Islamic religious material, especially in self-awareness and introspection. This is evidenced by a significant improvement in test scores through practice exercises. The practical implications of this research highlight the importance of implementing innovative and interactive learning methods in Islamic education to enhance student learning achievement.